2011
DOI: 10.1259/bjr/23130739
|View full text |Cite
|
Sign up to set email alerts
|

Brachytherapy for tongue cancer in the very elderly is an alternative to external beam radiation

Abstract: Background: The result of curative treatment for very elderly patients with tongue carcinoma has not been reported to date. We retrospectively reviewed the results of brachytherapy in 125 the patients aged over 75 years. Methods: The results of brachytherapy in 125 patients, 75 years old or older, with Stage I or II squamous cell carcinoma of the oral tongue were reviewed. The 125 cases consisted of 31 Stage I and 94 Stage II cases; 67 patients were under 80 years old and 58 were over 80 years old. All patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…BT alone for BOT cancer can be used for salvage treatment, in the setting of recurrent or new disease in previously irradiated fields, with reported median OS ranging from 11 months to 5 years . Although there are no reported studies of de novo BT only for BOT cancer, a study by Khalilur et al reported outcomes of elderly patients (over 75 years old) with early stage oral tongue cancer treated with BT, with a 3 year OS of 57%, similar to the results of our study . Thus, BT alone could possibly be used for patients with early stage BOT tumors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…BT alone for BOT cancer can be used for salvage treatment, in the setting of recurrent or new disease in previously irradiated fields, with reported median OS ranging from 11 months to 5 years . Although there are no reported studies of de novo BT only for BOT cancer, a study by Khalilur et al reported outcomes of elderly patients (over 75 years old) with early stage oral tongue cancer treated with BT, with a 3 year OS of 57%, similar to the results of our study . Thus, BT alone could possibly be used for patients with early stage BOT tumors.…”
Section: Discussionsupporting
confidence: 86%
“…32 Although there are no reported studies of de novo BT only for BOT cancer, a study by Khalilur et al reported outcomes of elderly patients (over 75 years old) with early stage oral tongue cancer treated with BT, with a 3 year OS of 57%, similar to the results of our study. 33 Thus, BT alone could possibly be used for patients with early stage BOT tumors.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid aging of Japan's population, the incidence rates of tongue cancer with advanced age are also rising [ 10 ]. Most of these patients cannot undergo invasive surgery, brachytherapy using 192 Ir hairpins or 197 Cs needles, or chemoradiation [ 7 ]. One of the curative treatment modalities left is 198 Au grains, because these grains can be applied under local anesthesia without producing pain or discomfort [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these patients cannot undergo invasive surgery, brachytherapy using 192 Ir hairpins or 197 Cs needles, or chemoradiation [ 7 ]. One of the curative treatment modalities left is 198 Au grains, because these grains can be applied under local anesthesia without producing pain or discomfort [ 7 ]. Our results showed that the differences in the cause-specific survival and local control rates between the Au-group and the Ir-group were less than 17%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation